Residual stress analysis and measurement in multi-layer bellows. (December 2021) - Lin, Jian; Wang, Xibo; Lei, Yongping; Ding, Jianchun; Li, Kangli; Guo, Fu
Abstract: Because large plastic deformation occurs in hydroforming bellows there is a residual stress distributing in the metal after forming, which is complex and not easy to be measured. The existence of residual stress might have an effect on the corrosive property and bulking performance of bellows. A finite element model was established to simulate the forming residual stress of the nickel alloy multi-layer bellow. The distribution of residual stress was calculated out and validated by cos α X-ray diffraction measurement. Thus the forming mechanics and the effects of layer number and forming pressure on the residual stress in the hydroforming bellow were both discussed in detail based on the established model. It was shown that the calculated residual stress had the same trend with the experimental results. The axial and circumferential residual stresses at the outer surface of the peak were both compressive. There existed the maximal Von Mises stress at the inner surface of the peak of the bellow. At this position the radial and axial residual stresses were both tensile. When applying multi-layer bellows and less forming pressure a lower forming residual stress could be obtained because of the narrow plastic strain region during forming.